2017
DOI: 10.18632/oncotarget.15361
|View full text |Cite
|
Sign up to set email alerts
|

Reduced E-cadherin facilitates renal cell carcinoma progression by WNT/β-catenin signaling activation

Abstract: Reduced expression of E-cadherin was observed in renal cell carcinoma (RCC). However, its potential clinical value and correlation with WNT/β-catenin signaling in RCC progression was still unclear. Immunohistochemical staining was performed in RCC tissue microarray to examine the expression status and prognosis value of E-cadherin and β-catenin. The potential role of E-cadherin in β-catenin translocation was analyzed with immunobloting assays. A significant negative correlation was observed between E-cadherin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…High or preserved membranous E-cadherin-expression was significantly associated with both worse OS and worse CSS. This is a novel finding with regard to former studies reporting on an association with worse outcome and loss of membranous E-cadherin-expression [15][16][17].…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…High or preserved membranous E-cadherin-expression was significantly associated with both worse OS and worse CSS. This is a novel finding with regard to former studies reporting on an association with worse outcome and loss of membranous E-cadherin-expression [15][16][17].…”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, some authors could also find a relationship between reduced E-cadherin expression and worse CSS [15,16] or RFS [26]. In some studies, no association between E-cadherin-expression and survival could be found [27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations